The Effect of Outpatient Health Services on the Satisfaction of BPJS Healthcare Participants at Madani Regional Hospital Pekan Baru - Muhammad Razie; Asriwati Asriwati; Ramadhani Syafitri Nasution (Universitas Ibn Khaldun Bogor, 2024)
This study evaluates the impact of outpatient health services on BPJS Health participant satisfaction at Madani Pekan Baru Regional Hospital in 2023. Quantitative research methods with a cross-sectional study approach were used. The results of univariate analysis show respondents' perceptions of service characteristics and aspects. Bivariate analysis highlighted significant relationships between responsiveness, reliability, assurance, caring, and patient satisfaction. Multivariate analysis using logistic regression confirmed that responsiveness and caring influence patient satisfaction. The implications are improvements in health worker response, service reliability, better communication, and facility maintenance.